Digital Payment Phenomenon as a Community Transaction Solution - Asfirah, Evi; Erawati, Desi; Hidayati, Tri (International Journal of Health, Economics, and Social Sciences (IJHESS), 2024)
Digital payments are growing along with technological developments, trends for millennials, many conveniences and advantages are felt by business people and the government, but there is still rejection from various parties, especially the elderly, this is still new and they are not used to use technology, which they consider complicated, and still consider cash more effective, is a challenge for the government to actively carry out literacy about digital payments, so that their use is more evenly distributed, no doubt a transaction solution in this day and age. This digital payment is a social fact that occurs, based on Auguste Comte's social theory that there are three stages of social development. The purpose of this research is to find out the phenomenon of digital payments and find out the advantages and disadvantages in terms of Auguste Comte's theory. This research uses qualitative research methods with library research from primary data sources of journal articles, news, documentation and observation through related social media. This phenomenon is part of the social changes that occur in the development of society. Changes are natural and driven by various factors, such as technological developments, lifestyle changes and supporting digital financial inclusion.